Influence Factors on the Radiation Temperature Measurement Accuracy of Turbine Blades - Li, Xunfeng; Yan, Hao; Zhao, Shu’nan; Cheng, Keyong; Chen, Junlin; Huai, Xiulan (Journal of thermal science, 2025)
Backward Monte Carlo method of the complicated and exact three-dimensional turbine with the spectral emission and reflection characteristics of the turbine blades materials and the spectral absorption and emission characteristics of combustion gas is established. The factors affecting the accuracy of the radiation temperature measurement are analyzed. The results show that reducing the distance from the probe to the target surface can reduce the effect of the environment on the measurement accuracy. Increasing the temperature and emissivity of the target surface can improve the measurement accuracy. The reflection characteristics of the surfaces have little influence on the radiation temperature measurement, so the blades can be considered as diffuse reflectors in order to improve the calculation efficiency. The temperature measurement accuracy decreases rapidly as the temperature of the combustion gas increases. The temperature measurement accuracy decreases with the increase of total gas pressure and H 2 O concentration. When measuring the temperature of rotating blades, the apparent emissivity of the target surface is inversely proportional to the measurement accuracy.